On limit theorems for the renewal processes - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Алешкявичене. Некоторые предельные теоремы для процессов восстановленияA. Aleškevičienė. Kai kurios atstatymo procesų ribinės teoremos